Edukasi Pengendalian Nyamuk Anopheles Sebagai Vektor Penyakit Malaria - Daawia, Daawia; Suyono, Ignatius Joko; Ngamelubun, Geraldinalia (LPPM Uncen, 2025)
This Community Service Activitiy on controlling Anopheles mosquitoes as vectors of malaria was carried out in Yamta Village, PIR 2, Arso District. The location was chosen because of the high number of malaria cases in Arso District, including Yamta Village. Education on controlling Anopheles mosquitoes as vectors of malaria was carried out through counseling and Forum Group Discussion (FGD) methods to increase public awareness of the dangers of malaria which can cause death, especially for mothers and children. In addition, education was also provided on eradicating mosquito nests by cleaning the community environment. Counseling on the use of mosquito nets that had been distributed by the government to the community was also encouraged. In addition to providing education through counseling, activities were also carried out to clean houses and the surrounding environment to eradicate mosquito nests in houses and in yards and gardens through a participatory planning approach involving the community. Community service was carried out to clean bushes and puddles of water which are breeding grounds for malaria vector mosquitoes.